Radiology (McGraw-Hill Education, 2009)
McGraw-Hill Specialty Board Review: Radiology is an outstanding review for both residents-in-training and practicing radiologists. You’ll find everything you need in this one comprehensive resource . . . questions, answers, detailed explanations, and targeted coverage that emphasizes key material in a simple, straightforward manner and reinforces important concepts.